Food security in Vietnam during the 1990s: The empirical evidence - Vasco Molini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Analysing the performance of ten developing countries, Hoddinot and Yohannes (2002) find a strong association between two measures of food security (calorie intake and mostly dietary diversity) and the increase in expenditures per capita. Using various indicators of food security, we describe the changes in food balances in Vietnam and find evidence of a substitution of poor micronutrients items (rice and cereals) with rich ones like fruit, vegetables fish and meat. Poor households, while increasing the amount of calories consumed, still lack vitamins, iron, calcium, etc. A preliminary assessment of the food security variation showed that improvements were, as expected, more concentrated among the richer Vietnamese households than the poor ones, although there was some improvement among poorer strata as well. We also focus on the calorie/expenditure elasticity and compare results for the years 1993 and 1998. Our findings confirm that this link is strong, and show that calorie income elasticity changed in the expected direction. We conclude that in general food security improved in Vietnam during 1990s although considerable differences still remain among expenditure deciles and among regions due to the accentuated spatial difference.
Keywords: I31; O15; Q18; 330; food security; calorie consumption; Vietnam; Vietnam; Ernährungsgewohnheit